Toxicidade e Gatilhos: Um Estudo de Caso em Comunidades do Reddit no Brasil - Piorino, Giovana; Lima, Luiz Henrique Quevedo; Pagano, Adriana Silvina; Silva, Ana Paula Couto da (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
In this work, we aim to understand linguistic features that may indicate potential triggers fostering toxic behavior among users in Portuguese-speaking Reddit communities. Our findings show that discussions involving such triggers tend to concentrate political terms and insults, shift topics more frequently, and make greater use of subordinating conjunctions.